“APRONTE-SE PARA MORRER”: OS MERETRÍCIOS E AS VIOLÊNCIAS CONTRA MULHERES MERETRIZES NA CIDADE DO CRATO-CE ATRAVÉS DA IMPRENSA E DE PROCESSOS JUDICIAIS (1940-1950) - CARDOSO, Ravenna Rodrigues (2023)
The iam of this research is to problematize the forms of violence that female prostitutes were exposed to. Whether physical or symbolic. Our time frame covers the 40s and 50s of the 20th century. And the spatial section is demarcated in the city of Crato, a city in the interior of Ceará, in the Cariri region. In addition to the central issue, which is violence, we also sought to reflect on the right to the city, especially for marginalized groups, with an emphasis on the female prostitutes who lived in this space. We were also able to establish relationships with the medical and criminological discourse present in Crato's newspapers with the theories of the Positive School, with Lombrosian arguments about prostitution. We used Moral Panic (COHEN), Precarious Life (BUTLHER) and Symbolic Violence (BOURDIEU) e Estigma (GOFFMAN) as our conceptual framework. As a methodological procedure for analyzing the versions contained in the lawsuits and newspapers, we used some apparatus from Discourse Analysis (DA) (FOUCAULT). We understand discourse as a practice of producing meaning that is directly linked to the conditions and circumstances in which it is produced (ORLANDI, 2009).